BIOLOGICAL PECULARITIES OF EPICOMETIS HIRTA PODA. AND METHODS OF ITS HARMFULNESS LIMITATION IN INDUSTRIAL PLANTS OF STRAWBERRIES IN FOREST STEPPE ZONE OF UKRAINE - Яновський, Ю. П.; Cуханов, С. В.; Cуханов, С. В.; Михайленко, Л. П.; Чепернатий, Є. В. (Scientific Progress & Innovations, 2015)
It is showed the results of studies where the biological peculiarities of Epicometis hirta Poda. are ascertained in industrial plants of strawberries in the right bank of Forest Steppe zone of Ukraine. It is established that beetles fly in warm sunny days the most intense from 10 a.m. to 15 p.m. and after 18 p.m. and in cool nights beetles hide in the soil in the depth of 0,5–2,5 cm. Pest has started to harm plants of strawberry starting of phase «nomination of peduncles» to the end of phase «end of flowering and the formation of ovaries» without any preferring of varietal origin. Copulation of individuals was started immediately after beetles appearing on the soil surface and lasted until the end of the adults fly. During the first half of May till the end of June active pests’ eggs laying in the soil on a depth of 35 cm was observed. The potential production of one female (2–3 hours) has reached 34–44 eggs, she postponed 12–17 eggs in the soil in several places. Larvae hatching from eggs was observed in II-decade of May and continued until the end of the III decade of July. The larvae lived in the soil by the end of August – early September and was fed by plant remains. The pupation phase was started from the end of August and lasted until half of September. After 15-20 days there were young beetles that stayed wintering in the soil (in untreated plots) till the next spring. In time of absence of protective measures to 93 % of flower of plants in plantations were damaged by this pest, their productivity was reduced to 65 %. For decrease of this pest population it is required to apply insecticide Mospilan, RP (0,2 kg/ha) and Calipso 480 SC, (0,25 l/hа).